Studi Analisis Psikologi Belajar Pendidikan Agama Islam Berdasarkan Kreativitas, Minat, Bakat, dan Intelegensi - Daswati, Daswati; Fitriani, Wahidah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This research provides a more holistic and in-depth understanding of the interplay between creativity, interest, talent, and intelligence in the context of Islamic Religious Education (PAI) learning. Employing a library research method, this study follows several steps, including literature source identification, selection and screening, information gathering, analysis, and synthesis. The outcomes of this library research reveal that: 1) Creativity plays a crucial role in enabling students to apply religious teachings innovatively in their daily lives. 2) Students with a strong interest in PAI tend to exhibit greater enthusiasm and eagerness in exploring religious concepts. 3) Acknowledging and leveraging students' talents in specific domains also contribute to a more meaningful learning experience and enhance student engagement in the learning process. 4) Both cognitive and emotional intelligence play a role in effectively understanding and applying religious teachings in daily life. The implications of these findings underscore that an instructional approach integrating creativity, interest, talent, and intelligence can assist in creating more engaging, relevant, and effective learning experiences within the realm of Islamic Religious Education.